Malignant conversion of benign right ventricular outflow track ventricular tachycardia 18 years post-ablation - Wendy H. Gerstein, MD; Neal S. Gerstein, MD; Andrea Sandoval, MD; Michael B. West, MD (Journal of Arrhythmia, 2015)
This case report describes the rare phenomenon of malignant conversion of benign right ventricular outflow tract ventricular tachycardia into idiopathic ventricular fibrillation 18 years after successful ablation, in the absence of any type of heart disease. We review the current literature looking at predictors for this event, with the conclusion that there are no reliable risk predictors available. Until clear guidelines exist, we suggest patients be informed and monitored for the possibility of “malignant conversion” following ablation for benign idiopathic outflow tract ventricular tachycardia.